THE INFLUENCE OF HEALTH EDUCATION USING THE ROLE MODEL ON MOLAR CARIES PREVENTION BEHAVIOUR IN PRIVATE ELEMENTARY SCHOOLS IN KENDARI CITY: HEALTH EDUCATION USING THE ROLE MODEL - Tasnim, Tasnim; Erfiani, Mery (STIKes Mandala Waluya Kendari, 2025)
Background: The prevalence of dental caries in private elementary school children is still high in Kendari City, Southeast Sulawesi Province. Elementary school children's knowledge about how to prevent dental caries is still lacking. Thus, encouraging less preventive behavior towards dental caries. Therefore, dental health education for school children needs to be carried out. This study aims to analyze the influence of Health Education with role model media on the behavior of preventing caries in permanent first molar teeth in private elementary schools in Kendari City. Methods: This study recruited 105 private elementary school students in Kendari City, namely Hidayatullah and Al-Fath. This research was conducted in July-December 2023. The research variables include knowledge, attitudes and actions towards the prevention of dental caries as dependent variables, and Health Education with the role model method is the independent variable. Data analysis using the Wilcoxon test. Results: This study suggests that Health Education with role model method influences knowledge, attitudes, and actions towards preventing caries in permanent first molar teeth (p<0.05). Conclusion: Health education using the role model method encourages behavioral changes towards preventing dental caries.